Laboratory animal weighing station with Beckman TOXSYS Terminal (1978)
A dead rat on a scale is being weighed to collect data used in chemical analyses of its tissues. The weighing station itself is manufactured by IBM.
Keywords: IBM computers; Rats as laboratory animals; Beckman Instruments, Inc.